Reducing academic stress levels by humorous shows among students: Penurunan tingkat stres akademik melalui tayangan humor pada mahasiswa - Siti Samsidar Lubis; Yunita Zahra (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
This study aims to see a decrease in academic stress levels through humorous shows to students during the covid-19 pandemic. During online lectures during the pandemic, students experience difficulties that can trigger students to experience academic stress. This experimental study used a repeated measures design and involved 17 students. The method of data analysis was carried out using the Wilcoxon test and the Friedman test. The results of this study indicate a decrease in the level of academic stress using humor for students. It can be seen from the academic stress level of students is lower after being given a humor show than before being given a humor show.